Analisis Perbandingan Kinerja Keuangan Antara Perbankan Syariah Dengan Perbankan Umum Devisa Nasional - Mufidha Miranti; Isfenti Sadalia (Jurnal Media Informasi Manajemen, 2013)
ABSTRACT   The purpose of this study was to determine differences in the financial performance of the Capital Management Ratio (capitalmanagement), Asset Quality Ratio (assetquality), Efficiency Ratio (efficiency), Profitability Ratio (profitability), and Ratio Liquidity Management (liquidity management) between Islamic banking common foreign and national banks in Indonesia Stock Exchange Data collection was performed by collecting secondary data from annual financial reports of Islamic banking with commercial banking of national income, consisting of the balance sheet and income statement banks period 2009-2011. The method used is descriptive analysis quantitatively using independent sample t-test (t test), with a significance level (α) = 5%. Analyzing data using statistical data processing software SPSS for windows. The results of hypothesis testing by T test showed that twenty financial ratios studied, none of that ratio has a positive and significant impact on the financial performance of Islamic banking and commercial banking national income. Keywords: Financial Performance, BankFinancial Ratios, Shariah Banking, Foreign and National Banking